Peran Alat Pembelajaran Edukatif dalam Peningkatan Akademik di SDN 3 Bluluk Lamongan - Cahyono, Andhika; Pudji, Soffia; Poniman, Poniman; Ridho Saputro, Andre; Ilahiyah, Al Ma’rifati (Fakultas Ekonomi Universitas Islam Majapahit, 2025)
Academics include teaching and learning, knowledge, skills and achievements obtained in the field of education. Educational learning tools are a development of educational game tool products (APE). An educational learning tool that aims to improve students' ability to absorb the subjects given at school in order to obtain increased grades in the academic world. SDN III Bluluk Lamongan has the problem of improving the effective teaching process in order to improve the quality of teaching and learning and grades. academics at school. The implementation method used in community service activities this time has 5 stages, the first is the observation method, the second is the introduction method, the third is the learning method, the fourth is the assessment method and the fifth is the sustainability method. The result of the service is an educational learning tool in the form of a modified snakes and ladders game that can improve students' grades and enthusiasm for learning and the role of this educational learning is to help students absorb lessons using a game method that can be played individually or in groups, and can be applied in various subjects.